Faktor yang Menyebabkan Kecemasan Ibu Hamil Trimester III dalam Menghadapi Persalinan di Puskesmas Depok 2 - Halil, Asni; Puspitasari, Elika (Jurnal Kesehatan, 2023)
The gestation period begins when fertilization occurs, namely when the egg cells produced by the ovarium and sperm cells meet. Anxiety in pregnancy was a negative emotional state that involves worry about pregnancy such as one's condition and the condition of the fetus, the process of giving birth to be passed, and the problem of readiness to become a mother. This study aims to determine the relationship between age, educational, parity and occupational with anxiety levels. This type of research was a quantitative method using a cross-sectional approach. The population in this study were all third-trimester pregnant women with a sample size of 50 subjects. The research instrument used was HARS questionnaire. Bivariate analysis used was the chi-square statistical test. The results showed that most respondents experienced moderate anxiety (31 respondents: 62%). There were 33 respondents (66%) who become housewives. The majority of the last education of respondents was senior high school (39 respondents: 78%). The parity of respondents was primigravida in majority (28 respondents: 56%). There were 43 respondents (86%) in the age category of <20 and >35 years old. The results of the bivariate analysis showed that there was a relationship between work and the anxiety level of pregnant women (p-value 0.041), and there was no relationship between the anxiety level of pregnant women and age (p-value 0.340) parity (p-value 0.288), and education (p-value 0.553).